Comparison between 90‐degree and 360‐degree selective laser trabeculoplasty (SLT): A 2‐year follow‐up. Issue 4 (15th October 2018) - Tawfique, Kozar; Khademi, Pardis; Quérat, Laurence; Khadamy, Joobin; Chen, Enping
Abstract: Purpose: To compare the effect of 90‐ and 360‐degree selective laser trabeculoplasty (SLT) as primary or supplement therapy in patients with glaucoma and ocular hypertension (OHT). Methods: Patients (>30 years old) with OHT, primary open‐angle glaucoma (OAG), pigmentary glaucoma or pseudoexfoliative glaucoma were enrolled in a prospective randomized clinical trial. Patients were sequentially randomized to either 90‐ or 360‐degree SLT. Their intraocular pressure (IOP) was monitored. Results: The survival periods (in days) of the two extents (90 or 360 degrees) of treatment were not statistically significantly different (p = 0.85); only pretreatment IOP level could predict survival of treatment (p = 0.02). Conclusion: The 90‐degree SLT is as effective as 360‐degree SLT. Further studies are warranted to confirm the findings. High baseline IOP could be a factor that predicts treatment success.